The microbiome in graft-versus-host disease: a tale of two ecosystems - Hamed Soleimani Samarkhazan; Sina Nouri; Mohsen Maleknia; Mojtaba Aghaei (Journal of Translational Medicine)
Abstract Graft-versus-host disease (GVHD), a life-threatening complication of allogeneic hematopoietic stem cell transplantation (HSCT), is shaped by a dynamic interplay between two microbial ecosystems: the recipient’s disrupted microbiome and the donor’s transplanted microbiota. This narrative review unravels the “tale of two ecosystems,” exploring how pre-transplant chemotherapy, radiation, and antibiotics induce recipient dysbiosis—marked by loss of beneficial taxa (Clostridia, Faecalibacterium) and dominance of pathobionts (Enterococcus). These shifts impair barrier integrity, fuel systemic inflammation, and skew immune responses toward pro-inflammatory T-cell subsets, exacerbating GVHD. Conversely, emerging evidence implicates donor microbiota in modulating post-transplant immune reconstitution, though its role remains underexplored. Therapeutic strategies, including probiotics, prebiotics, and fecal microbiota transplantation (FMT), demonstrate promise in restoring microbial balance, enhancing short-chain fatty acid (SCFA)-driven immune regulation, and reducing GVHD severity. However, challenges such as strain-specific efficacy, safety in immunocompromised hosts, and protocol standardization persist. By bridging microbial ecology and immunology, this review underscores the microbiome’s transformative potential in redefining GVHD management and advocates for personalized, microbiome-targeted interventions to improve HSCT outcomes.